Dynamics of the acute viral hepatitises morbidity and range of medicinal preparations for treatment in hospital environment in the Volgograd region (the Russian Federation), 2016–2018. - L. M. Ganicheva; E. A. Ioannidi; O. A. Panfilova; I. N. Tyurenkov; Yu. S. Knyazeva; N. Sh. Kaisheva (Фармация и фармакология (Пятигорск))
The aim of the study was to investigate the prevalence of acute viral hepatitises A, B and C in the Volgograd region; the range and identification of the most frequently prescribed pharmacological groups to be used in hospital environment; and analyzing the price dynamics of medicines. These factors will make it possible to assess the state of the medicine provision for the patients with this disease in hospital environment. Materials and methods. In the study, the following methods have been used: comparison, a method of grouping indicators and a structurallogical method. The materials were the hepatological department patients’ treatment sheets (Volgograd Regional Clinical Infectious Diseases Hospital N1).Results. Acute hepatitis A is the most common (46.9%), acute hepatitis B occupies the second position (27.4%), and acute hepatitis C – the third one (25.7%), where in 46.2%, 23.5% and 14.7%, respectively, are accounted for by icteric viral hepatitis. Hepatoprotectors, symptomatic medications and rehydration and detoxification medicinal preparations are prescribed for all forms and degrees of the disease severity.Conclusion. The study has revealed a decreased morbidity of acute viral hepatitises A, B and an increased morbidity of acute viral hepatitis C in the Volgograd region. Among all the types of hepatitises, the prevailing one is the icteric form of moderate severity. The range of medicinal preparations prescribed for the treatment of acute viral hepatitises has been studied. Most often, doctors prescribe hepatoprotectors, rehydration and detoxification medicinal preparations. The study of price dynamics, showed a predominant increase in hepatoprotectors and a decrease in medicines for rehydration and detoxification. The results obtained indicate a tendency towards the improvement of drug provision in the Volgograd Region, for the patients with acute viral hepatitises. Besides, the results of the study give an opportunity to consider the ways of its further optimization.